Characteristics of Severe Acute Respiratory Syndrome Coronavirus-2 Infection and Comparison With Influenza in Children Admitted to U.K. PICUs. (15th March 2021) - Kanthimathinathan, Hari Krishnan; Buckley, Hannah; Lamming, Caroline; Davis, Peter; Ramnarayan, Padmanabhan; Feltbower, Richard; Draper, Elizabeth S.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Severe acute respiratory syndrome coronavirus-2 affects adults disproportionately more than children. A small proportion of children with severe acute respiratory syndrome coronavirus-2 required admission to a PICU. We describe the nationwide U.K. PICU experience of severe acute respiratory syndrome coronavirus-2 infection during the first wave of the pandemic and compare this with the critical care course of the 2019 influenza cohort. Design: Prospective nationwide cohort study of characteristics of severe acute respiratory syndrome coronavirus-2–positive children. Data collection utilized routine Pediatric Intensive Care Audit Network and severe acute respiratory syndrome coronavirus-2–specific data. Setting: All U.K. PICUs. Patients: Children less than 18 years old, admitted to U.K. PICUs between March 14, 2020, and June 13, 2020, and a positive severe acute respiratory syndrome coronavirus-2 polymerase chain reaction. Children admitted to U.K. PICUs in 2019 with influenza provided comparison. Interventions: None. Measurements and Main Results: We identified 76 PICU admissions among 73 children with a positive severe acute respiratory syndrome coronavirus-2 polymerase chain reaction test. Prevalence of PICU admissions per million was 5.2 for children versus 260 for adults. Ten children (14%) were identified on routine screening. Seventeen children (23%) had pediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus-2. Seventeen (23%) had coinfections. Invasive ventilation was required in seven of 17 children (41%) with pediatric inflammatory multisystem syndrome temporally associated with severe acute respiratory syndrome coronavirus-2 versus 38 of 56 other severe acute respiratory syndrome coronavirus-2 positive children (68%), with 77% requiring vasoactive support versus 43%, respectively. Seven children (10%) died. In comparison with influenza children, severe acute respiratory syndrome coronavirus-2 children were older (median [interquartile range]: 10 [1–13] vs 3 yr [1–8 yr]), more often Black or Asian (52% v 18%), higher weight z score (0.29 [–0.80 to 1.62] vs –0.41 [–1.37 to 0.63]), and higher deprivation index (3.3 [–1 to 6.3] vs 1.2 [–1.8 to 4.4]). Comorbidities, frequency of organ supports, and length of stay were similar. Conclusions: This nationwide study confirms that PICU admissions with severe acute respiratory syndrome coronavirus-2 infections were infrequent. We have reported similarities and differences in sociodemographic characteristics, organ support interventions, and outcomes of children affected by severe acute respiratory syndrome coronavirus-2 compared with influenza.